The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0886260518796526
|View full text |Cite
|
Sign up to set email alerts
|

“Stop Waking the Dead”: Internet Child Sexual Abuse and Perspectives on Its Disclosure

Abstract: The phenomenon of Internet child sexual abuse (ICSA) has been receiving growing attention over the last decade, and studies have promoted knowledge with respect to the phenomenon's epidemiology, as well as to characteristics of the victims, perpetrators, and dynamics in these cases. The current retrospective study sought to delve into the disclosure component in cases of ICSA. The sample comprised 52 cases of adolescents who arrived at a child advocacy center (CAC) following ICSA. Analysis of these cases was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Issues were also raised about how trust could be established with practitioners where there was limited shared understanding about what had happened, the technologies that had been used, and the need of the CYP to try and maintain control over what had happened. Many studies have noted the reluctance of CYP to disclose their experiences of OCSA ( 35 ), and in one of the first studies in this area most children did not disclose, and even when confronted with the photographic evidence of the abuse, they would only acknowledge what they thought was already known ( 33 ). This would seem to suggest that only a few children who have experienced OCSA will be identified, and even fewer will be provided with meaningful therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
“…Issues were also raised about how trust could be established with practitioners where there was limited shared understanding about what had happened, the technologies that had been used, and the need of the CYP to try and maintain control over what had happened. Many studies have noted the reluctance of CYP to disclose their experiences of OCSA ( 35 ), and in one of the first studies in this area most children did not disclose, and even when confronted with the photographic evidence of the abuse, they would only acknowledge what they thought was already known ( 33 ). This would seem to suggest that only a few children who have experienced OCSA will be identified, and even fewer will be provided with meaningful therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
“…Although the research on internet-initiated sexual abuse and commercial sexual exploitation suggests that adolescents may be particularly reluctant to disclose, it is important to consider the way in which different types of abuse victims are discovered. Adolescent victims of internet-initiated sexual abuse are usually discovered through online chats, images, or other corroborative evidence (Katz, 2013; Katz et al, 2021; Leander et al, 2008). In Katz (2013) none of the adolescent victims had disclosed abuse before the formal interview, and other studies have found similarly small percentages of prior disclosure (Katz et al, 2021: 6%; Leander et al, 2008: 4%).…”
Section: Reluctance and How Abuse Is Discoveredmentioning
confidence: 99%
“…Examining 20 11- to 14-year-old victims of internet-initiated sexual abuse, Katz (2013) found that 8 of the 20 victims (40%) refused to cooperate with the interviewers, even rejecting efforts at rapport building. In a sample of 52 11- to 17-year-olds victimized online, Katz et al (2021) found that 20 victims (38%) “refused to disclose anything” (p. NP5095), though an unspecified number ultimately gave some information. Studies examining interviews with adolescent CSE victims also find that reluctance is common.…”
Section: Adolescent Victims’ Reluctance To Disclose Sexual Abusementioning
confidence: 99%
“…evidence is discovered before the child is questioned about abuse. Studies examining documented abuse have found high rates of reluctance and denial (Katz, Piller, Glucklich, & Matty, 2018;Leander, 2010;Sjöberg & Lindblad, 2002).…”
Section: Recent Evidence Of Abuse Denialmentioning
confidence: 99%
“…Another promising approach is to examine cases for which there is photographic or digital evidence of abuse, which can establish ground truth, reduce substantiation bias, and even solve the suspicion bias problem if the digital evidence is discovered before the child is questioned about abuse. Studies examining documented abuse have found high rates of reluctance and denial (Katz, Piller, Glucklich, & Matty, 2018; Leander, 2010; Sjöberg & Lindblad, 2002).…”
Section: Recent Evidence Of Abuse Denialmentioning
confidence: 99%